1977
DOI: 10.1111/j.1365-2265.1977.tb01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles and Cardiovascular Disease in the Whickham Area With Particular Reference to Thyroid Failure

Abstract: SUMMARY The age and sex distribution of ischaemic heart disease (IHD), other vascular disorders and serum lipid concentrations and the possible association between these factors and thyroid failure have been examined in a community survey. A past history of IHD occurred in 7.5% of males and 4.8% of females.‘Chest pain on effort’was found in 7.4% of males and 7.8% of females and‘possible infarction’in 5.4% of males and 3.8% of females. Major ECG changes were found in 4.7% of both sexes and minor changes in 6.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
3
2

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 28 publications
5
72
3
2
Order By: Relevance
“…26,27 One community-based study has reported higher mean systolic and diastolic blood pressures in women with elevated TSH. 28 However, the analysis was not stratified by age and the women with elevated TSH were significantly older than their euthyroid controls. This same study found no difference in the mean systolic and diastolic blood pressures of hypothyroid and euthyroid men, although unlike the women, these two groups of men were of similar ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 One community-based study has reported higher mean systolic and diastolic blood pressures in women with elevated TSH. 28 However, the analysis was not stratified by age and the women with elevated TSH were significantly older than their euthyroid controls. This same study found no difference in the mean systolic and diastolic blood pressures of hypothyroid and euthyroid men, although unlike the women, these two groups of men were of similar ages.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] While hypothyroidism is identified as a cause of diastolic hypertension in many medical textbooks [8][9][10][11] and in review articles 1,12 research based on non-referred subjects is contradictory about the association. [13][14][15] Hypothyroidism and diastolic hypertension are both common and have prevalences which increase with age. In the community setting overt hypothyroidism occurs in 1.5% to 2% of women and 0.2% of men.…”
Section: Introductionmentioning
confidence: 99%
“…However, a precise relationship between overt hypothyroidism and CAD has not been confirmed, although data linking these two conditions have been demonstrated in autopsy studies (1,2). Subclinical hypothyroidism (SH), defined as the clinical status of elevated serum thyrotropin (TSH) levels, with normal levels of thyroxine (T 4 ) and triiodothyronine (T 3 ), is a more common disorder than overt hypothyroidism with a prevalence of 1.4 -7.8% in older populations and even greater percentiles among women (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Overt hypothyroidism is associated with abnormalities of lipid metabolism, which may predispose to the development of atherosclerotic coronary artery disease (CAD) (1,2). However, a precise relationship between overt hypothyroidism and CAD has not been confirmed, although data linking these two conditions have been demonstrated in autopsy studies (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation